New cases of human diphyllobothriosis in Patagonia, Argentine - Liliana Semenas; Ana Kreiter; Javier Urbanski (Universidade de São Paulo, 2001)
The purpose of the paper is to describe 4 new cases of human diphyllobothriosis in Patagonia, Argentine. Adult parasites recovered were submitted to morphological and histological analyses for taxonomic identification. The etiological agent found was always Diphyllobothrium latum and all the cases were autochthonous. These data combined with previous information make the number of autochthonous human cases of diphyllobothriosis registered in Argentina increase to 18.